Social Intolerance in Pakistani Male Youth, its Damages and Solutions in the Light of Islamic Teachings - Muhammad Rafi Chan; Ayaz Akhter; Muhammad Tahir Malik; Haris Bilal; Hafiz Faisal Sharif (Al-Qanṭara, 2024)
Islam is a religion of peace and promotes tolerance and encourages believers to interact among themselves in a respectful and compassionate manner. Regarding Sahaba the close fellows Quran says they are harsh against the nonbelievers but merciful among themselves)[1]. This article investigates the intricate dynamics of social intolerance within the Pakistani male youth demography, offering insights into its origins, far-reaching consequences, and potential remedies grounded in Islamic teachings. Employing a multidimensional research approach, this study blends sociological, psychological, and religious perspectives to provide a nuanced understanding of the phenomenon. Utilizing a combination of qualitative and quantitative methodologies, the research seeks to unravel the contributing factors behind the emergence of social intolerance among Pakistani male youth. The article illuminates the diverse damages inflicted by social intolerance, ranging from strained interpersonal relationships to broader societal discord. By examining its repercussions on mental health, community cohesion, and national unity, the research underscores the urgency of addressing this issue for the overall well-being of Pakistani society. In the pursuit of viable solutions, the article turns to Islamic teachings as a guiding framework. These teachings are synthesized into practical strategies and interventions tailored to resonate with the distinctive cultural and religious context of Pakistani male youth to foster tolerance, understanding, and harmony. This, in turn, promises to cultivate a more inclusive and cohesive societal fabric. Key words: Social intolerance, Islamic teachings, peace, respect, harmony, male youth